Reenvisioning Language Anxiety in the Globalized Classroom Through a Social Imaginary Lens. Issue 3 (28th May 2015) - De Costa, Peter I.
<x xml:space="preserve">Abstract</x> The last three decades have witnessed a notable growth in research on affect. Among the various affective variables, foreign language anxiety has been heavily studied. This interest in foreign language anxiety is consistent with increased attention to emotions in the neurosciences, cognitive psychology, and the social sciences. Instead of attempting to establish a grand unified theory on affect, this article focuses on and reenvisions the affective variable of language anxiety while recognizing that second language acquisition has benefited much from earlier research insights. In taking an interdisciplinary approach and drawing on the notion of the social imaginary, this study also seeks to expand the field's current theoretical horizon and respond to calls for epistemological diversity in the field of second language acquisition.